The Question of Takfir from the Sunni Perspective: A Theological and Jurisprudential Inquiry - Muhammad Uthman El-Muhammady, Asma; M. Zein, Ibrahim (Jurnal Usuluddin, 2025)
This study examines the theological and jurisprudential dimensions of takfir the act of declaring a fellow Muslim a disbeliever from the perspective of mainstream Sunni. Drawing on classical sources, particularly the works of al-Ghazali, it delineates the definitional boundaries of kufr and the conditions under which takfir may be legitimately applied. Qualitative in nature, the analysis emphasizes the Sunni tradition’s insistence on ‘restraint’ from takfir; the presumption of Islam, and the dangers of misapplication of takfir in contexts of interpretive disagreement (taʾwil). Central to the discussion is al-Ghazali’s framework, including his five levels of existence and his requirement of definitive proof (qat‘i), which collectively underscore that takfir must rest on an explicit denial (takzib) of prophetic teachings and incontrovertible rejection of what is known by necessity in religion (ma‘lum min al-din bi al-darurah). The paper argues that sectarian polemics and interpretive errors (ta’wil) cannot serve as grounds for takfir. By situating takfir within the methodology of the salaf, the study demonstrates that Sunni thought categorically rejects indiscriminate takfir and upholds the sanctity of Muslim unity and doctrinal tolerance, provided that such tolerance does not contravene the essential definition of kufr.